The Law Enforcement on Criminal Acts of Narcotics Abuse by Child - Akmadi Akmadi; Gunarto Gunarto; Deny Suwondo (Universitas Islam Sultan Agung, 2022)
The purpose of this study was to determine and analyze law enforcement against the crime of narcotics abuse by children. To find out and analyze the obstacles in law enforcement against the crime of narcotics abuse by children. To find out and analyze efforts to overcome the obstacles of criminal acts of narcotics abuse by children. This study used an empirical juridical approach, with descriptive research specifications. The data used in this study was secondary data obtained through literature study which was then analyzed qualitatively. The results of this study are Law Enforcement Against Criminal Acts of Narcotics Abuse by Children are The government and state institutions should provide special protection for children, and most specifically for children who are in conflict with the law and children who are victims of narcotics abuse. The problem is: Law enforcement officers or legal structures here are limited to the police, prosecutors and judges. Facilities and facilities in law enforcement are less supportive and incomplete. Community participation and control in some areas are still very low due to a sense of not caring about their own environment even though it is clearly seen directly that there are acts of narcotics abuse. The quality and quality of some police officers who work in the Res Unit are still low. The efforts are: Increased understanding of the concept of diversion with restorative justice is aimed at law enforcement officers (both for the police, prosecutors and judges). Must try to develop potential or human resources in the Res Unit. Drugs through participating in further training on narcotics and the modes in their distribution, so that in the future members of the Res Unit. Drugs have the ability and are more maximal in seeking law enforcement against narcotics crimes. Inviting all elements of society because in accordance with the law the community plays a role in handling, preventing, and distributing narcotics.